Personal finance management mobile application - Pow, Kah Meon (2025)
This project is concerned with the design and development of a Personal Finance Management Mobile Application to be utilized for helping users, particularly students and young professionals, manage their financial activities efficiently via a smartphone platform. It tackles some of the key problems, such as inefficient expense tracking, no budgeting discipline, and no access to integrated financial planning tools. This app simplifies record keeping and classifying of income and expenses, makes budgets and monitors saving goals, monitors each saving goal, and reminds one when to pay certain bills. In addition, the application has its own loan calculator that estimates each repayment scheme and there is a real-time currency converter in case one handles multiple currencies. The system was developed using the Agile methodology, enabling iterative refinement through continuous feedback and testing. Android Studio was the primary development environment, while secure and real-time data storage were provided by Firebase Firestore. UI/UX design was implemented using Figma to maximize usability, and graphical data visualization tools were also incorporated within the application to enable users to track spending trends and understand their financial habits. Overall, the project aims to promote financial literacy, enable informed decision-making, and provide a reliable digital solution for personal finance management.